Groups 4 Health versus cognitive–behavioural therapy for depression and loneliness in young people: randomised phase 3 non-inferiority trial with 12-month follow-up. (March 2022) - Cruwys, Tegan; Haslam, Catherine; Rathbone, Joanne A.; Williams, Elyse; Haslam, S. Alexander; Walter, Zoe C.
Abstract : Background: Depression treatments are typically less effective for young people than for adults. However, treatments rarely target loneliness, which is a key risk factor in the onset, maintenance and development of depression. Aims: This study evaluated the efficacy of a novel loneliness intervention, Groups 4 Health (G4H), relative to the best-practice treatment of cognitive–behavioural therapy (CBT) in reducing loneliness and depression over a 12-month period (Australian New Zealand Clinical Trial Registry: ACTRN12618000440224). Method: The study was a phase 3 randomised non-inferiority trial comparing G4 H with dose-controlled group CBT. Participants were 174 people aged 15–25 years experiencing loneliness and clinically significant symptoms of depression, who were not in receipt of adjunct treatment. Participants were recruited from mental health services in Southeast Queensland, Australia. Randomisation was conducted using computer software. Follow-up assessments and statistical analyses were masked to allocation. Both interventions consisted of five 75 min group-based psychotherapy sessions. The primary outcomes were depression and loneliness, with a non-inferiority margin of 2.20 for depression. Results: The trial enrolled 174 participants between 24 April 2018 and 25 May 2019, with 84 in the G4 H condition and 90 in the CBT condition. All randomised participants were included in the intention-to-treat analyses ( n = 174). The pre–post effect sizes for depression were d G4H = −0.71 and d CBT = −0.91. For loneliness, they were d G4H = −1.07 and d CBT = −0.89. At 12-month follow-up, the absolute difference between groups on depression was 1.176 (95% CI −1.94 to 4.29) and on loneliness it was −0.679 (95% CI −1.43 to 0.07). No adverse effects were observed. Conclusions: G4H was non-inferior to CBT for depression and showed a slight advantage over CBT for loneliness that emerged after treatment completion.